Lakon Wahyu Makutharama sebagai Refleksi Penanaman Nilai-Nilai Pancasila - Akhmad Rifqi Muawam (Institut Seni Indonesia Surakarta, 2021)
This article discusses the correlation between wayang and Pancasila’s values also the potential of Chapter Makutharama as a means of conveying the meaning of Pancasila. The method used in this discussion is the case study method, so that the deepening of the elements of wayang can be found in its potential as a means of conveying Pancasila. The results showed that in general fact both the puppets and the Pancasila had similarities in their content, namely humanity. Further examination of the complexity of the puppets shows that every point of the Pancasila’s precepts is also included in the puppet. The knowledge of Hastha Brata that contained in the Chapter Wahyu Makutharama is able to convey the values of Pancasila. The insight about leadership qualities which refers to the eight characteristics of the natural elements, namely: sun, moon, stars, clouds, earth, ocean, fire, and wind, is proven to reflect the Pancasila. With the complexity of wayang’s elements, Hastha Brata in Chapter Wahyu Makutharama can be used as an aesthetic contemplation. The delivery of the meaning of Pancasila in this new way is expected to be a turning point for the return of Pancasila in every people’s life of the Unitary State of the Republic of Indonesia.